2013
DOI: 10.1016/j.brat.2013.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Cognitive Therapy for PTSD in routine clinical care: Effectiveness and moderators of outcome in a consecutive sample

Abstract: ObjectiveTrauma-focused psychological treatments are recommended as first-line treatments for Posttraumatic Stress Disorder (PTSD), but clinicians may be concerned that the good outcomes observed in randomized controlled trials (RCTs) may not generalize to the wide range of traumas and presentations seen in clinical practice. This study investigated whether Cognitive Therapy for PTSD (CT-PTSD) can be effectively implemented into a UK National Health Service Outpatient Clinic serving a defined ethnically mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 55 publications
10
93
3
1
Order By: Relevance
“…Interestingly, this range is comparable with the existing literature, where some studies have reported TEs near zero (e.g. Ehlers et al, 2013;Elkin et al, 2006;Owen, Tao, & Rodolfa, 2010) while other studies have reported TEs of 10% or higher (e.g. Boswell, Castonguay, & Wassermann, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, this range is comparable with the existing literature, where some studies have reported TEs near zero (e.g. Ehlers et al, 2013;Elkin et al, 2006;Owen, Tao, & Rodolfa, 2010) while other studies have reported TEs of 10% or higher (e.g. Boswell, Castonguay, & Wassermann, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Although replication is needed, our finding does suggest that a lack of habituation to anxiety during the early stage of iPE treatment can be used to detect those patients that are unlikely to benefit from exposure-based treatment. Also, patients living alone were more likely to belong to the Partial-responders cluster than to the Non-responders cluster, which result is in contrast to previous findings (Ehlers et al, 2013; Tarrier et al, 2000; van Minnen et al, 2002). However, it is possible that in our highly affected PTSD population, the presence of a partner helps maintain PTSD-related avoidance behaviour.…”
Section: Discussioncontrasting
confidence: 99%
“…In standard weekly TFT programmes, patients characteristics are not found to be stable predictors of treatment outcome (Ehlers et al, 2013; Ehring et al, 2014; Powers et al, 2010; van Minnen, Arntz, & Keijsers, 2002; van Minnen, Harned, Zoellner, & Mills, 2012) and findings concerning (early) treatment process variables, such as fear habituation, are inconsistent (Bluett, Zoellner, & Feeny, 2014; Sripada & Rauch, 2015; van Minnen & Hagenaars, 2002). This variability might be explained by the fact that in most studies prediction analyses of associations were performed in entire and thus heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…Within the Ehlers group's efficacy and effectiveness studies, in a typical 12 session CT-PTSD intervention, the site visit would be around session 9 (Ehlers et al 2003(Ehlers et al , 2005(Ehlers et al , 2013(Ehlers et al , 2014. As visiting the site can provoke a strong emotional response, many therapists will first work on other therapy tasks, such as reliving the memory in imagination, before visiting the site.…”
Section: When To Do a Site Visitmentioning
confidence: 99%
“…This article aims to promote the use of site visits in TF-CBT by providing a clear theoretical rationale for the technique (based predominantly around Ehlers & Clark, 2000;Ehlers et al 2003Ehlers et al , 2005Ehlers et al , 2013Ehlers et al , 2014, and presenting the available evidence regarding their use. A practical framework, with illustrative case examples, is also included, to guide therapists in how to plan and implement an effective site visit.…”
Section: Introductionmentioning
confidence: 99%